The historical Jesus a Sheffield reader - Porter, Stanley E. 1956-; Evans, Craig A. (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- teaching -- exegetical aspects; Jesus Christ -- teaching -- linguistic aspects; Jesus Christ -- person and offices